99.6k views
1 vote
Simplify this expression: (-2 - 8x) + (-4x - 10)

User Que
by
5.8k points

2 Answers

6 votes

Answer:

The answer is -12x - 12

Explanation:

-2 - 8x - 4x - 10

= -2 + -8x + -4x + -10

Combine like terms:

-2 + -8x + -4x + -10

(-8x + -4x) + (-2 + -10)

= -12x + -12

= -12x - 12

User Dreagan
by
5.9k points
5 votes

Answer:

The simplified form of expression (-2 - 8x) + (-4x - 10) is

-12(x + 1)

Explanation:

It is given an expression (-2 - 8x) + (-4x - 10)

To find the simplified expression of (-2 - 8x) + (-4x - 10)

Let expression is given by

(-2 - 8x) + (-4x - 10) = -2 - 8x -4x -10

= -2 -10 -4x -8x

= -12 -12x

-12(x + 1) (since -12 is common in both terms)

Therefore simplified form is -12(x + 1)

User Wah
by
5.7k points